Hypopituitarism, A Sequel to TBI - J Gordon Millichap; John J Millichap (Pediatric Neurology Briefs Publishers, 2014)
Investigators at Cincinnati Children's Hospital, OH, studied the prevalence of hypopituitarism in children with inflicted traumatic brain injury.